2021
DOI: 10.1021/acs.analchem.1c04660
|View full text |Cite
|
Sign up to set email alerts
|

Influenza AM2 Channel Oligomerization Is Sensitive to Its Chemical Environment

Abstract: Viroporins are small viral ion channels that play important roles in the viral infection cycle and are proven antiviral drug targets. Matrix protein 2 from influenza A (AM2) is the best-characterized viroporin, and the current paradigm is that AM2 forms monodisperse tetramers. Here, we used native mass spectrometry and other techniques to characterize the oligomeric state of both the full-length and transmembrane (TM) domain of AM2 in a variety of different pH and detergent conditions. Unexpectedly, we discove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 63 publications
(123 reference statements)
1
19
0
Order By: Relevance
“…It is important to note that the chronological sequence of α-syn associating with DMPG nanodiscs indicates that it does not strongly prefer specific oligomeric complexes. If specific complexes like dimers or tetramers were being formed, we would expect to see higher relative intensities for peaks with a stoichiometry of 2 or 4, as has been previously observed with certain antimicrobial peptide , and membrane protein complexes in nanodiscs. , Instead, we observe sequential association from one to six α-syn’s with no clear preferences. Complexes may still be forming, but without observable oligomeric specificity.…”
Section: Results and Discussionsupporting
confidence: 60%
“…It is important to note that the chronological sequence of α-syn associating with DMPG nanodiscs indicates that it does not strongly prefer specific oligomeric complexes. If specific complexes like dimers or tetramers were being formed, we would expect to see higher relative intensities for peaks with a stoichiometry of 2 or 4, as has been previously observed with certain antimicrobial peptide , and membrane protein complexes in nanodiscs. , Instead, we observe sequential association from one to six α-syn’s with no clear preferences. Complexes may still be forming, but without observable oligomeric specificity.…”
Section: Results and Discussionsupporting
confidence: 60%
“…We analyzed the E protein at pH values of 5.0, 7.0, and 9.0. Prior research on M2 had shown that pH significantly affected the oligomeric state . However, the pH of the solution did not influence E protein oligomerization (Figure S2), and only dimer was observed in all conditions.…”
Section: Resultsmentioning
confidence: 74%
“…Native MS uses nanoelectrospray ionization with nondenaturing solvent conditions to preserve noncovalent interactions and can keep proteins folded inside the mass spectrometer . Because each oligomeric species has a unique mass, native MS provides valuable information on polydisperse oligomers. We previously leveraged native MS to reveal the unexpected polydispersity of M2 from influenza A, which suggested that other viroporins may also display complex oligomeric behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile salts such as AmAc play another crucial role by providing a physiological ionic strength for the solution and establishing the pH . Previous studies have shown that the type of detergent used and salt concentrations both have significant effects on membrane protein oligomeric states and lipid binding characteristics. ,, Therefore, to develop the OBE for membrane protein analysis, we first exchanged the membrane protein, AqpZ, into mobile phases containing different amounts of detergents and salts.…”
Section: Resultsmentioning
confidence: 99%
“…Together, these results demonstrate the value of high-flow OBE with low-flow MS injections to study nanodiscs, which removes the need for manual injections with single-use needles. OBE-native MS could thus be used to screen nanodisc assembly conditions for homogeneity, to screen drug binding to membrane proteins inside the nanodisc, and to screen ligand binding and complex formation prior to EM studies, such as above with NB binding to MelB St (Figure ). The growing use of nanodiscs in membrane protein structural biology makes them important targets for native MS analysis in an integrated structural biology pipeline.…”
Section: Resultsmentioning
confidence: 99%